Добро пожаловать в сказку - Благов Владимир (Новые сказочные повести, 2010)
Экземпляры: ф14 (20130424) / Инвентарный номер: 48372 / Цена: 75.00 / Сис.шифр: Р2ср / Авт.знак: Б 68 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6